Formation of Мicroelement Сomposition of Soils of Semi-desert Landscapes of Stavropol Territory - T. V. Degtyareva; E. N. Solyannik; V. V. Melnichuk; E. A. Lyashenko (Наука. Инновации. Технологии, 2022)
Introduction: The article examines the features of the formation of the microelement composition of soils of two landscapes of the semi-desert landscape province of the Stavropol Territory - Pravokum-Tersky and Kursk-Caspian. The importance of studying the microelement composition of soils of semi-desert landscapes lies in determining the general laws characteristic of soils of arid territories in fixing chemical elements. The low level of agricultural use of these soils determines the weak influence of anthropogenic activities on the transformation of their microelement composition.Research materials and methods. The main methods of research were soil-geochemical, landscape-geochemical, geoecological. Field studies were carried out with the selection of soil samples, office work with the analysis of the content of trace elements (Cu, Zn, Pb, Cd) on an X-ray fluorescence spectrometer. An analysis of the available scientific publications on this topic was carried out, which made it possible to supplement the actual material received by the authors.Research results and discussion. It was established that the peculiarities of the formation of the microelement composition of soils of semi-desert landscapes of the Stavropol Territory are largely related to the specific conditions of soil formation inherent in this territory. A nonwashing type of water regime, an arid climate, semi-desert wormwood-cereal vegetation, a high carbonate content of the soil profile create characteristic features of the chestnut type of soil formation. Lateral differentiation of the microelement composition of soils of semi-desert landscapes is weakly manifested due to the almost complete absence of differences in surface slope.Conclusions. The microelement composition of soils of semi-desert landscapes of the Stavropol Territory is characterized by certain features associated with the manifestation of the main factors of soil formation. The fixation of trace elements in the soil profile is controlled by the processes of humus formation under sparse semi-desert vegetation, weakened vertical movement of soil formation products under conditions of non-washing water regime, high carbonation and, in some places, salinity of soil masses.